Complex Constellation of Gastroptosis, Achalasia, and Hypertophic Gastritis: A Case Report - Elvina Prisila; Rheycado Arrafi Pratama; Novi Wijayanti Sukirto; Salsabila Chairunnisa Ramadhani (Riviera Publishing, 2025)
The concurrent presentation of multiple upper gastrointestinal (GI) disorders is a rare clinical entity that poses significant diagnostic and therapeutic challenges. We present an unprecedented case of coexisting achalasia, gastroptosis, hypertrophic gastritis, and hyperacidity, which culminated in a life-threatening metabolic emergency. Case presentation: A 63-year-old female with a history of chronic dyspepsia presented with progressive nausea, vomiting, significant weight loss, and an acute episode of severe hypoglycemia (random blood glucose 52 mg/dL). A barium contrast study (Oesophagus-Maag-Duodenum) was the key diagnostic investigation. Radiological findings revealed a dilated esophagus with a distal